Real-Time Velocity Profile Generation Of Powder Conveying Using Electrodynamic Transducer - Rahmat, Mohd Fua'ad; Fazalul Rahiman, Mohd. Hezri (Penerbit UTM Press, 2001)
This methodology explores the probability in determining the real-time velocity profiles of a vertical and horizontal flow. Generally, the measurement is based on the electrostatic charges produced by dry solid powder during their movement in the flow rig and accumulated at the sensors’ electrode. Two arrays of dedicated electrodynamic sensors are used as static-to-electrical signal converter and they are located at the pipe wall. The sensors generated electrical signal corresponding to the amount of flow it detects and this is based on the fact that the amount of flow contributes to the level of the static charges accumulated at the sensors. The collected data is retrieved and manipulated by an application program, which is developed using Microsoft Visual Basic 6.0. The application features the ability to obtain velocity in real-time mode, which is previously unrealisable.